2007
DOI: 10.1210/en.2006-1035
|View full text |Cite
|
Sign up to set email alerts
|

Functional Desensitization of the Extracellular Calcium-Sensing Receptor Is Regulated via Distinct Mechanisms: Role of G Protein-Coupled Receptor Kinases, Protein Kinase C and β-Arrestins

Abstract: The extracellular calcium-sensing receptor (CaR) senses small fluctuations of the extracellular calcium (Ca(2+)(e)) concentration and translates them into potent changes in parathyroid hormone secretion. Dissecting the regulatory mechanisms of CaR-mediated signal transduction may provide insights into the physiology of the receptor and identify new molecules as potential drug targets for the treatment of osteoporosis and/or hyperparathyroidism. CaR can be phosphorylated by protein kinase C (PKC) and G protein-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
49
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 32 publications
2
49
0
Order By: Relevance
“…To date, GPCR internalization is characterized by the receptor phosphorylation by GRKs and/or second messengerdependent kinases, -arrestin binding, and subsequent receptor sequestration (26). In our experiments, inhibition and activation of PKC could prevent or promote the CCR9 internalization triggered by IL-2 and IL-4, which confirmed the participation of PKC in the process.…”
Section: Discussionsupporting
confidence: 82%
“…To date, GPCR internalization is characterized by the receptor phosphorylation by GRKs and/or second messengerdependent kinases, -arrestin binding, and subsequent receptor sequestration (26). In our experiments, inhibition and activation of PKC could prevent or promote the CCR9 internalization triggered by IL-2 and IL-4, which confirmed the participation of PKC in the process.…”
Section: Discussionsupporting
confidence: 82%
“…Although agonist-mediated endocytosis has been observed for several of the mGluRs, mGluR1 and mGluR5 additionally demonstrate constitutive internalization (48,49). CaSR is the closest related mammalian receptor of GPRC6A and has proven highly resistant to desensitization, which most likely reflects a persistent exposure to the endogenous agonist Ca 2ϩ (50,51). Constitutive internalization of CaSR has been observed in some studies (52,53), and moreover, a distinct regulatory mechanism for CaSR has been reported in which agonist stimulation triggers further insertion of receptors in the cell membrane from intracellular stores, thereby increasing the amount of receptors available for activation.…”
Section: Discussionmentioning
confidence: 99%
“…The receptor senses changes in extracellular calcium concentration ([Ca 2C ] o ) and activates different intracellular pathways (Ward 2004, Tfelt-Hansen & Brown 2005, Huang & Miller 2007, Lorenz et al 2007). In particular, CASR activation triggers calcium mobilization from intracellular stores through inositol trisphosphate (IP 3 ) receptors and activation of the mitogen activated protein kinase (MAPK) cascade through p44/42 extracellular signaling-regulated kinase (ERK) phosphorylation.…”
Section: Introductionmentioning
confidence: 99%